2013
DOI: 10.3747/co.20.1193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cancer on Ovarian Function in Patients Undergoing In Vitro Fertilization for Fertility Preservation: A Reappraisal

Abstract: The past decade has witnessed an increase in cancer survival rates[...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…As far as ovarian response is concerned, several studies have found a similar number of retrieved oocytes between cancer patients and the control group [18,20,21,[24][25][26][27], which is in agreement with the current findings. However, in one of the largest studies in which 223 cancer patients were included, patients with malignancy exhibited a weaker response to COH, especially those with hormone-dependent tumors.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As far as ovarian response is concerned, several studies have found a similar number of retrieved oocytes between cancer patients and the control group [18,20,21,[24][25][26][27], which is in agreement with the current findings. However, in one of the largest studies in which 223 cancer patients were included, patients with malignancy exhibited a weaker response to COH, especially those with hormone-dependent tumors.…”
Section: Discussionsupporting
confidence: 82%
“…The majority of published studies regarding ovarian reserve have not demonstrated significant differences between patients with malignancy and their age-matched controls [18][19][20][21], although some authors have reported significantly lower AMH levels in patients with lymphoma [22] and lower AFC in women with cancer than in healthy controls [23]. Analyzing the ovarian reserve status was not the main goal of the current study but the observed data do not seem to reveal diminished ovarian reserve ( Table 1).…”
Section: Discussionmentioning
confidence: 65%
“…Indeed, many authors have pointed out the need for higher amounts of exogenous FSH and a reduced number of oocyte recovered in cancer patients seeking FP when compared with infertile controls, suggesting altered response to gonadotropins and/or poorer follicular competence [4,5,[11][12][13]. Conversely, recent data failed to show any difference in ovarian response to stimulation between cancer patients and age-matched control subjects [6,[14][15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the studies have not demonstrated relevant differences in ovarian reserve and oocytes retrieved between women with cancer and the healthy group. Almog et al, in their study with 81 women, stated that the ovarian function was not affected by the type of cancer [65][66][67][68][69].…”
Section: Influence Of Cancer On Ovarian Functionmentioning
confidence: 95%